2020
DOI: 10.3390/rs12213520
|View full text |Cite
|
Sign up to set email alerts
|

RFI Suppression for SAR Systems Based on Removed Spectrum Iterative Adaptive Approach

Abstract: A synthetic aperture radar (SAR) system can be seriously contaminated by radio frequency systems because of working in the same microwave frequency bands, which would degrade the SAR image quality and affect the accuracy of image interpretation. In this paper, a novel radio frequency interference (RFI) suppression approach including RFI identification, band-stop filtering and a removed spectrum iterative adaptive approach (RSIAA) is proposed. First, the smoothing process is added before RFI signal detection to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In terms of RFI suppression methods, they This work is licensed under a Creative Commons Attribution 4.0 License. For more information, see https://creativecommons.org/licenses/by/4.0/ can be roughly divided into three categories: nonparametric [9], [10], [11], parametric [12], [13], [14], [15], and semiparametric [16], [17], [18], [19], [20], [21], [22], [23]. Among them, nonparametric methods normally focus on the setting of notching filters in the frequency domain, which can greatly suppress RFIs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of RFI suppression methods, they This work is licensed under a Creative Commons Attribution 4.0 License. For more information, see https://creativecommons.org/licenses/by/4.0/ can be roughly divided into three categories: nonparametric [9], [10], [11], parametric [12], [13], [14], [15], and semiparametric [16], [17], [18], [19], [20], [21], [22], [23]. Among them, nonparametric methods normally focus on the setting of notching filters in the frequency domain, which can greatly suppress RFIs.…”
Section: Introductionmentioning
confidence: 99%
“…This impact is especially evident when RFIs are wideband. Although a removed spectrum IAA is proposed in [11] to recover the damaged SAR signal spectrum, even so, when bandwidths of RFIs are relatively large, SAR signals are still difficult to be recovered perfectly. The common basic idea of parameter methods is the subspace projection.…”
Section: Introductionmentioning
confidence: 99%
“…Global navigation satellite system (GNSS), represented by global position system (GPS), is a space-based navigation and positioning system, which is widely used in various fields such as land, sea and air navigation, aerospace, geodesy, and other national defense construction and national economy with its full space coverage, all-weather work, and high positioning accuracy [1][2][3]. When the navigation signal arrives at the ground, the signal is already very weak, so it is susceptible to various intentional or unintentional interferences [4][5][6]. For military or core civilian areas, anti-jamming performance is an important indicator to evaluate the navigation receivers [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al [17] found that the trap filter had a significant effect on the side flaps of the system response, which may be considered as a false target; Wu et al [18] combine the advantages of traditional notching filtering and Eigen-subspace projection methods to reduce false alarm rates providing a more accurate determination of thresholds and gap weights. Instead of the method for processing data in the time and time-frequency domains, Xu et al [19] proposed an adaptive spectral iteration method to obtain the desired range spectra from the available neighbourhood spectral data. In a nutshell, the non-parametric method requires less computation and permits easier implementation [20], but faces the problem of spectral loss in the echo signal, which usually presents some significant side flaps in the image [21].…”
Section: Introductionmentioning
confidence: 99%